Большая книга развивающих игр для девочек: головоломки, логические игры, ребусы, загадки / В. Г. Дмитриева ; худож. И. Горбунова, Е. Жуковская - Дмитриева Валентина Геннадьевна (Астрель, 2010)
Экземпляры: СФ-2 (20111209) / Инвентарный номер: 40225z2 / Цена: 173.52 / Сис.шифр: 74.102 / Авт.знак: Д 53 / ББК: 74.102